2015
DOI: 10.1111/vec.12336
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dipyrone, meloxicam, or the combination on hemostasis in conscious dogs

Abstract: While meloxicam does not alter hemostasis by the methods evaluated, dipyrone inhibits platelet aggregation for up to 3 hours. Meloxicam-dipyrone combination causes more prolonged inhibition of platelet function than dipyrone alone. Decreased platelet aggregation induced by dipyrone and dipyrone-meloxicam does not appear to impact the viscoelastic properties of the blood clot nor increase the risk of bleeding in dogs without preexisting hemostatic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Finally, 2 dogs received meloxicam before admission. These dogs were not excluded from the study, in accordance with the results of a previous study in which the administration of meloxicam did not seem to alter hemostasis according to the methods evaluated (TEM and whole blood platelet aggregation) in dogs …”
Section: Discussionmentioning
confidence: 57%
“…Finally, 2 dogs received meloxicam before admission. These dogs were not excluded from the study, in accordance with the results of a previous study in which the administration of meloxicam did not seem to alter hemostasis according to the methods evaluated (TEM and whole blood platelet aggregation) in dogs …”
Section: Discussionmentioning
confidence: 57%
“…Although some previous studies demonstrate impairment of platelet function with use of NSAIDs, it is also important to note that many studies fail to demonstrate an inhibitory effect of NSAIDs on platelets. 4,10,14,16,45 The same is true regarding the use of carprofen in dogs. Multiple studies have demonstrated some impairment in platelet aggregation or tissue TXB2 concentrations, 9,27,43 while numerous other studies have failed to show an effect of carprofen use on primary hemostasis, TXB2, and 6-keto prostaglandin F1a.…”
Section: Discussionmentioning
confidence: 93%
“…1,30,38 It is also possible that changes in platelet activity could be dependent on the specific NSAID studied and the species in which the study is performed, particularly as this study examined the effects of a selective COX-2 inhibitor. 10,14,35,45 As COX-1, rather than COX-2, is more instrumental in production of TXA2 from prostaglandin H 2 , the selective COX-2 activity of the NSAID used in this study may preclude it from having an effect on platelet activation and growth factor release. 2,9,28 The observation that TXB2 was not decreased with use of the COX-2 inhibitor in this study suggests that these platelets were still able to produce thromboxane, probably via the COX-1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects were found in rats [33]. In dogs, however, there was no significant MET effect in level of WBC when given at a dose of 25 mg/kg [34]. With regard to piglet model, the effect of the MET on WBC also manifests the fluctuating course of the curve reporting on the effect.…”
Section: Discussionmentioning
confidence: 61%
“…Yet, in rat-based studies, MET administration induced a slight fall in Hct [33], while in dogs, no MET-induced effects were seen in Hct levels at a dose of 25 mg/kg [34]. Of note, the observed variability is substantial, however, the observed decrease is significant ( p  < 0.05).…”
Section: Discussionmentioning
confidence: 99%